Design and analysis of RF-CMOS switch for reconfigurable RF front end - Soeroso, Iksannurazmi Bambang (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The consumer demands on having multi-functional wireless communication devices have driven current mobile handset to be more complex than it has ever been before. Of interest, radio frequency (RF) front end has evolved to adapt to multi-standards terminals. Therefore, having an RF-CMOS switch that suits this purpose can be considered unprecedented. This work presents the design and analysis of RF-CMOS switch for reconfigurable RF front end. The RF-CMOS switch is based on two typical designs of transmit-receive (T/R) switch mainly single pole single throw (SPST) and single pole double throw (SPDT) topologies. These designs are analyzed based on key figures of merit of T/R switches, namely insertion loss, isolation and power handling capability. In order to determine the switches performance, the simulation for each key figure of merit is done for two specific designs, namely design A and design B. These designs are varied in terms of their transistor widths. The simulation is done using Cadence Virtuoso software tool and utilizing standard 0.35µm CMOS technology. The SPST RF-CMOS switch exhibits insertion loss of 1.155dB while the SPDT RF-CMOS switch exhibits insertion loss of 1.153dB at 2GHz. On the other hand, the isolation for both RF-CMOS switch designs is kept high (>20dB). Nonetheless, the RF-CMOS switch exhibits power handling capability measured by power 1dB compression point (P1dB) of (>20dBm) and third order intercept point (IIP3) of (>26dBm). On top of that, a DC bias condition needed to operate the switch is discussed to determine an optimal bias condition for each RF-CMOS switch design. This work also presents the capability of integrating the RF-CMOS switch with SAW resonator through simulation. Indeed, this simulation demonstrates the application of RF-CMOS switch for reconfigurable RF front end.